Low inflation bends the Phillips Curve around the world - Forbes, Kristin,Gagnon, Joseph E.,Collins, Christopher G. (MIT Sloan School of Management, 2020)
This paper models inflation by combining the multi-country framework of one of its authors (Forbes) with the nonlinear specification proposed by the other two (Gagnon and Collins). The results find strong support for a Phillips curve that becomes nonlinear when inflation is low, in which case excess economic slack has little effect on inflation. This finding is consistent with evidence of downward nominal wage and price rigidity. The estimates also show a significant and economically meaningful Phillips curve relationship between slack and inflation when slack is negative (i.e., when output is above long-run potential). In this nonlinear model, international factors play a large role in explaining headline inflation, a role that has increased over time, supporting the results of Forbes' linear model
10.2139/ssrn.3577993
Keywords: Graue Literatur; Economic slack; globalization; output gap; price dynamics